THE EFFECT OF COMPENSATION, TRANSFORMATIONAL LEADERSHIP STYLE, INTRINSIC MOTIVATION ON EMPLOYEE PERFORMANCE THROUGH JOB SATISFACTION IN THE CUSTOMER SATISFACTION MANAGEMENT DIVISION PT. BUKALAPAK.COM TBK - Edi Sugiono; Muhamad Febriyadi; Rio Mattajang (Jurnal Ekonomi, 2022)
This study aims to determine the effect of compensation, transformational leadership style, intrinsic motivation on employee performance through job satisfaction in the Customer Satisfaction Management Division of PT. Bukalapak.Com Tbk. The method used in this study is a quantitative method and hypothesis testing is carried out with SEM analysis techniques. The results of this study indicate that compensation has a negative and insignificant effect on job satisfaction, transformational leadership style and intrinsic motivation have a positive and significant effect on job satisfaction. Compensation has a positive and insignificant effect on employee performance, transformational leadership style has a negative and significant effect on employee performance, intrinsic motivation and job satisfaction have a positive and significant effect on employee performance. Compensation has a negative and insignificant effect on Employee Performance through Job Satisfaction, Transformational Leadership Style has a positive and insignificant effect on Employee Performance through Job Satisfaction, Intrinsic Motivation has a positive and significant effect on Employee Performance through Job Satisfaction.